Differential Interleukin‐8 thresholds for chemotaxis and netosis in human neutrophils. Issue 9 (4th June 2021) - Teijeira, Alvaro; Garasa, Saray; Ochoa, Maria del Carmen; Cirella, Assunta; Olivera, Irene; Glez‐Vaz, Javier; Andueza, Maria Pilar; Migueliz, Itziar; Alvarez, Maite; Rodríguez‐Ruiz, Maria Esperanza; Rouzaut, Ana; Berraondo, Pedro; et al.
Abstract: In humans, IL‐8 (CXCL8) is a key chemokine for chemotaxis of polymorphonuclear leukocytes and monocytes/macrophages when acting on CXCR1 and CXCR2. CXCL8 activity on neutrophils includes chemotaxis and eliciting the extrusion of neutrophil extracellular traps (NETs). In this study, we show that concentrations of IL‐8 that induce NETosis surpass in at least one order of magnitude those required to elicit chemoattraction in human neutrophils. IL‐8‐induced NETosis was less dependent on G‐proteins than migration, while extracellular Ca +2 chelation similarly inhibited both processes. Reactive oxygen species (ROS) were more important for NETosis than for chemotaxis as evidenced by neutralization with N‐acetyl ‐cysteine. Interestingly, selective blockade with anti‐CXCR1 mAb inhibited NETosis much more readily than chemotaxis, while pharmacological inhibition of both CXCR1 and CXCR2, or selective inhibition for CXCR2 alone, similarly inhibited both functions. Together, these results propose a model according to which low concentrations of IL‐8 in a gradient attract neutrophils to the inflammatory foci, while high receptor‐saturating concentrations of IL‐8 give rise to NETosis once leukocytes reach the core of the inflammatory insult. Abstract : Interleukin‐8 can induce chemotaxis and NETosis in human peripheral blood neutrophils. This paper shows that at low concentrations, IL‐8 preferentially induces chemotaxis while NETosis is mainly promoted at high IL‐8 concentrations. IL‐8 induced NETosis and chemotaxis have different receptor and signaling requirements.